Kemampuan Guru PAI dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) Kurikulum 2013 di SMP Nurul Hadina - Al Husnah, Miftah; Neliwati; Fathurrahman, Muhammad (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the ability of Islamic religious education teachers in preparing 2013 Curriculum Learning Implementation Plans (RPP) at SMP Nurul Hadina Patumbak. This research uses a qualitative approach with a descriptive study method. Data collection techniques by conducting interviews with PAI teachers, observation and documentation in the form of lesson plans that have been made by the teacher. The results of this study found that the ability of Islamic religious education teachers to prepare Learning Implementation Plans (RPP) at Nurul Hadina Patumbak Middle School was categorized as good with evidence of Learning Implementation Plans (RPP) that had been made by the teacher, this can be seen from the completeness of the RPP made by the teacher concerned .